Strategic planning in education : making change happen - Miclat, Eusebio F. (Manila, Philippines : Rex Book Store, 2005)
The preparation and formulation of a strategic plan, be it in education, business and voluntary organizations, is by no means and easy task. It requires the participation of many individuals and groups.
Chapter 1. strategic planning: concepts, theories, and practices -- Chapter 2. the planning process -- Chapter 3. implementing the plan -- Chapter 4. plan evaluation.
Includes bibliographical references and index.
Keywords: EDUCATION